Hierarchical Risk Factors for Stunting in Urban Indonesian Children (0–59 Months): A Case‒Control Study from Jambi, Indonesia - Huntari Harahap; Irawan Anasta Putra; Nisa Haska Maulina; Erny Kusdiyah; Nurul Qalbi Alrani; I Made Dwi Mertha Adnyana (Research and Development Center for Food, Nutrition and Public Health (P4GKM) LPPM UNS, 2025)
Stunting affects 149.2 million children globally, with Indonesia reporting a prevalence of 21.6%, despite a decline in trends. Urban-specific risk factors remain poorly characterized, which limits the development of effective intervention strategies for metropolitan areas. This study aimed to identify the risk factors associated with stunting in children aged 0 to 59 months in Jambi, Indonesia. This case-control study involved 108 children aged 0 to 59 months from five community health centers in Jambi City from December 2024 to January 2025. The cases (n = 54) were children with height-for-age z scores of less than 2 standard deviations (SD), and the controls (n = 54) had standard growth patterns. Data collection involved anthropometric measurements and structured maternal interviews, which were analyzed via chi-square tests with 95% confidence intervals. Low birth length had a very high odds ratio (OR = 45.69, 95% CI = 5.88 to 354.70; p < 0.001), whereas inadequate complementary feeding resulted in a perfect prediction (OR = 5.33, 95% CI = 3.20 to 8.88; p < 0.001). Incomplete immunization (OR = 37.81, 95% CI = 8.32 to 171.71; p < 0.001) and maternal educational deficit (OR = 6.53, 95% CI = 1.76 to 24.18; p = 0.002) were identified as the primary modifiable determinants. Multisectoral strategies targeting maternal nutrition, universal immunization, and education-based interventions are necessary to reduce stunting in Indonesia’s urban population sustainably.